2016
DOI: 10.1002/ca.22787
|View full text |Cite
|
Sign up to set email alerts
|

The orbit: A re‐appraisal of the surgical landmarks of the medial and lateral walls

Abstract: The anterior ethmoidal foramen (AEF) and posterior ethmoidal foramina (AEF and PEF, respectively) on the medial wall and the cranio-orbital foramen (COF) on the lateral wall are used as landmarks in orbital surgeries. In surgery these foramina, the neurovascular structures they transmit and other orbital structures in close proximity need to be identified to minimise their risk of damage. Despite the clinical importance, the current understandings lack consistency in the precise location, microanatomy and morp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Our findings support previous studies that identified accessory foramina among heterogeneous ethnic groups at frequencies of between 28.5% and 47% . Further, the literature has shown accessory foramen in 37% of African‐American and 39.9% of Chinese skulls, which coincides with our findings.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings support previous studies that identified accessory foramina among heterogeneous ethnic groups at frequencies of between 28.5% and 47% . Further, the literature has shown accessory foramen in 37% of African‐American and 39.9% of Chinese skulls, which coincides with our findings.…”
Section: Discussionsupporting
confidence: 93%
“…However, recent anatomic studies have suggested that up to 6 branches can be present within a single orbit. A number of studies have described osteometric quantification of the ethmoid foramina as a surrogate for the number of actual ethmoidal arteries, with most studies analyzing heterogeneous ethnic cohorts. However, established ethnic differences in orbital morphology suggest that there may be concomitant significant differences in the presence and symmetry of supernumerary ethmoidal vessels across patient groups.…”
mentioning
confidence: 99%
“…HC has been used [25,26]. It has also been named the cranioorbital foramen [9,36] meningo-orbital foramen [11,29,30], lacrimal foramen [17,21], and orbitomeningeal foramen [21,28]. HC and its other names are not listed in the 1998 Terminologia Anatomica [31].…”
Section: Discussionmentioning
confidence: 99%
“…It is essential to know the microanatomy of the orbit and its neurovascular relations before undertaking any kind of surgery in this region. The surgical approaches directed to the orbit should be planned according to several characteristics, such as; the size, location, and anatomical relations of the related pathology and the least invasive possible technique which provides the greatest anatomical control should be chosen to decrease surgery related complications such as strabismus, ptosis, reflex losses, and weakness in eye movements (Maroon and Kennerdell, 1984; Rhoton, ; Abdel Aziz et al, ; Altay et al, ; Yoon and Pather, ).…”
Section: Microsurgical Anatomy Of the Orbital Segment Of The Oculomotmentioning
confidence: 99%